EFFECTIVENESS OF RANGE OF MOTION ON REDUCING PAIN LEVELS IN ELDERLY OSTEOARTHRITIS IN JATIRAHAYU COMMUNITY HEALTH CENTER, BEKASI - Saka Adhijaya Pendit; Dayu Ningsih; Steviani Imaculata (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
Background:Problems often faced by the elderly in physical conditions that begin to weaken, resulting in degenerative diseases such as arthritis or Osteoarthritis. Osteoarthritis has the right treatment to relieve pain in the joints. In this Osteoarthritis, the right technique will be carried out, namely non-pharmacological with ROM (Range Of Motion) movements. aims to determine the effect of providing ROM (Range Of Motion) interventions on reducing pain levels in the elderly with osteoarthritis in the Jatirahayu Bekasi Health Center area. Method: The population in this study was 37 elderly people. This sample was taken with a total of 10 respondents. This study is a study that uses a Quasi Experimental research design, with a one group pre-test post-test approach. Results: Using the Paired Sample T-Test. Based on the results of the study, the results obtained with the Paired Sample T-Test obtained a mean of 3.60000, Std. Deviation 0.96609, and Sig. (P Value) 0.000 < 0.05 concluded that there was an influence between the results of the decrease in pain scale on the data before and after ROM intervention was given. The results stated that the pain scale of respondents before and after ROM intervention was given was effective.